2020
DOI: 10.1016/j.ceramint.2019.09.232
|View full text |Cite
|
Sign up to set email alerts
|

Graphene triggered enhancement in visible-light active photocatalysis as well as in energy storage capacity of (CFO)1-x(GNPs)x nanocomposites

Abstract: triggered enhancement in visible-light active photocatalysis as well as in energy storage capacity of (CFO)1-x(GNPs)x nanocomposites. Ceramics International, (2020). 46.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…9 The results demonstrate that incorporating GNPs with MFO nanoparticles could considerably improve the photocatalytic efficiency up to a certain optimum GNPs loading ratio and then decreases beyond that ratio. The decrease in photocatalytic activity has been observed previously and might be because of the visible shielding produced by GNPs [72]. From the experimental results, it can be inferred that the degradation of MB dye is governed by the synergistic contribution of two possible mechanisms i.e., photocatalytic and photo-Fenton reaction as presented in Fig.…”
Section: Photocatalysissupporting
confidence: 67%
“…9 The results demonstrate that incorporating GNPs with MFO nanoparticles could considerably improve the photocatalytic efficiency up to a certain optimum GNPs loading ratio and then decreases beyond that ratio. The decrease in photocatalytic activity has been observed previously and might be because of the visible shielding produced by GNPs [72]. From the experimental results, it can be inferred that the degradation of MB dye is governed by the synergistic contribution of two possible mechanisms i.e., photocatalytic and photo-Fenton reaction as presented in Fig.…”
Section: Photocatalysissupporting
confidence: 67%
“…Their study showed that the introduction of graphene increased the photocatalytic activity for the degradation of methylene blue from 38.3% to 98.7%. This was because graphene slowed down the recombination of electron-hole pairs in semiconductors [166]. Yan et al, (2020) prepared a graphene/polypyrrole composite and obtained a 94.8% removal efficiency of phenol using photocatalytic degradation [167].…”
Section: Photocatalysismentioning
confidence: 99%
“…So maximum number of electrons enter in conduction band from the grapheme. As a result higher concentration of GNPs provide more π-electrons to transfer the conduction band of CFO nanostructures (Israr et al, 2020).…”
Section: Uv-visible Spectroscopy Analysismentioning
confidence: 99%